Influence of Principal Leadership Styles, Teachers’ Job Satisfaction, Work-Related Flow on Teachers’ Productivity in Iwo Local Government Area of Osun State, Nigeria - SANNI, Kamorududeen Taiwo; ARANSI, Waliyi Olayemi; ESAN, Oyemomi Mope; AYODELE, Omobolanle Janet (Ilorin Journal of Education, 2024)
The study explored the influence of leadership styles, job satisfaction and work-related flow on teachers’ productivity in Iwo Local Government Area of Osun state, Nigeria. Four specific objective and research questions were deduced and answered, while two hypotheses were tested. The study employed descriptive survey research design. Purposive and simple random sampling techniques were employed to select wo-hundred and fifty participants. The instrument tagged ‘Work-Related Flow Questionnaire’ (WRFQ), ‘Leadership Styles Questionnaire’ (LSQ), Job Satisfaction Questionnaire (JSQ) and ‘Teachers’ Productivity Questionnaire’ (TPQ) were used. Regression was used for data analysis. The result indicated that there is a significant change in teachers’ productivity level due to the effective application of leadership style principles by the head of the school. Also, it was revealed that there is a significant change in teachers’ productivity level due to the level off job satisfaction maintained by teachers. The empirical results show that principal style, job satisfaction and teachers work-related flow are factors that explain 51.5% of the observed variation in teachers’ productivity. The study concluded that leadership style, job satisfaction and work-related flow positively influenced teachers' productivity. The study recommended that the school principals should be encouraged to adapt their leadership style to the needs of their school and staff, create a supportive and positive work environment that allows teachers to feel a sense of flow and satisfaction in their work, recognize and reward teachers for their hard work and achievements, which can help to increase their sense of satisfaction among others.